General Health In Saudi Arabia: Health Workers As Drivers Of Population Health And System Transformation (The Review of Diabetic Studies, 2024)
General health in Saudi Arabia is influenced by rapid socioeconomic changes, demographic shifts, and evolving disease patterns. Health workers play a key role in translating national health priorities into population-level outcomes. This article examines general health in Saudi Arabia, concentrating on the impact of health workers on health promotion, disease prevention, and system performance. Through a population health and workforce-centered approach, the paper highlights how healthcare professionals address non-communicable diseases, strengthen primary care, and improve health system performance. The analysis emphasizes the importance of investing in the health workforce to sustain improvements in overall health across the Kingdom.